Numerical Investigation of Flow Field Characteristics Around a Monopile Foundation with Collar Protection - Lei Wu; Hao Meng; Haifei Sun; Lingfei Yu; Dake Chen; Xiyu Zhao; Dawei Guan (Journal of Marine Science and Engineering, 2025)
Collar structures are widely used to protect monopile foundations from scour, but their geometric obstruction hinders direct observation of the surrounding flow in physical experiments. To overcome this limitation, this study employs large-eddy simulation (LES) to investigate the flow characteristics around a monopile with collar protection. The LES model was validated against well-documented experimental data of pile-induced flow, confirming its reliability. Simulations under flat-bed and equilibrium scour conditions were conducted to evaluate the effects of the collar on time-averaged velocity, vortex dynamics, and turbulence intensity. The results show that the collar substantially weakens the upstream accelerated flow, suppresses horseshoe vortex formation, and reduces both the strength and extent of sidewall currents. Under flatbed conditions, the side-flow intensity decreases by 24.3% and the accelerated flow area is reduced by 93.3%. A counter-rotating vortex beneath the collar dissipates kinetic energy and simplifies the near-bed vortex system, thereby mitigating scour. However, the protective effect diminishes with increasing inflow velocity, with turbulence intensity rising by 159% for a 14% velocity increase. Overall, this study provides deeper insights into the protective mechanisms of collar structures, advancing the understanding of their effectiveness and limitations in monopile scour protection.